2013
DOI: 10.1016/s0968-8080(13)41691-9
|View full text |Cite
|
Sign up to set email alerts
|

Improving quality of life with new menstrual hygiene practices among adolescent tribal girls in rural Gujarat, India

Abstract: The Government of India has started a new scheme aimed at offering sanitary pads at a subsidized rate to adolescent girls in rural areas. This paper addresses menstrual health and hygiene practices among adolescent girls in a rural, tribal region of South Gujarat, India, and their experiences using old cloths, a new soft cloth (falalin) and sanitary pads. Qualitative and quantitative data were collected in a community-based study over six months, with a pre-and post- design, among 164 adolescent girls from eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
101
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(109 citation statements)
references
References 4 publications
5
101
1
2
Order By: Relevance
“…All of the interventions evaluated have been published since 2000. Seven of these studies were conducted in South Asia, 5359 whereas the other studies were done in Ghana, 60 Tanzania, 61 Iran, 62 and Saudi Arabia 63 (Table 2). …”
Section: Interventions To Improve Menstrual Hygiene Management In Resmentioning
confidence: 99%
“…All of the interventions evaluated have been published since 2000. Seven of these studies were conducted in South Asia, 5359 whereas the other studies were done in Ghana, 60 Tanzania, 61 Iran, 62 and Saudi Arabia 63 (Table 2). …”
Section: Interventions To Improve Menstrual Hygiene Management In Resmentioning
confidence: 99%
“…Studies have shown that most of the women do not use sanitary pads during their menstruation. 8,9 Menstrual hygiene and social taboos are issues needs to be addressed at all levels. The issues of poor menstrual hygiene management have been ignored or misunderstood by the society as well as the policy makers.…”
Section: Introductionmentioning
confidence: 99%
“…The issues of menstrual hygiene discussed through health education are an essential resource for improving menstrual hygiene in women especially in less developed countries. 8,10 Thus, it is essential to design a mechanism to address and for the access of healthy menstrual practices. 3,8 There is a need to educate and empower women about safe and hygienic practices during menstruation and bring them out of traditional beliefs, taboos and misconceptions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is based on tradition passed down for generations as in the older days there were no napkins and many used old cloths as napkins [8]. In addition, many believe that if used SNs are not washed before being thrown away, one risks being afflicted with hysteria and disturbances and is unhygienic.…”
Section: Introductionmentioning
confidence: 99%